Dissociation and its biological and clinical associations in functional neurological disorder: systematic review and meta-analysis. Issue 1 (1st January 2023) - Campbell, Malcolm C.; Smakowski, Abigail; Rojas-Aguiluz, Maya; Goldstein, Laura H.; Cardeña, Etzel; Nicholson, Timothy R.; Reinders, Antje A. T. S.; Pick, Susannah
Abstract : Background: Studies have reported elevated rates of dissociative symptoms and comorbid dissociative disorders in functional neurological disorder (FND); however, a comprehensive review is lacking. Aims: To systematically review the severity of dissociative symptoms and prevalence of comorbid dissociative disorders in FND and summarise their biological and clinical associations. Method: We searched Embase, PsycInfo and MEDLINE up to June 2021, combining terms for FND and dissociation. Studies were eligible if reporting dissociative symptom scores or rates of comorbid dissociative disorder in FND samples. Risk of bias was appraised using modified Newcastle–Ottawa criteria. The findings were synthesised qualitatively and dissociative symptom scores were included in a meta-analysis (PROSPERO CRD42020173263). Results: Seventy-five studies were eligible (FND n = 3940; control n = 3073), most commonly prospective case–control studies ( k = 54). Dissociative disorders were frequently comorbid in FND. Psychoform dissociation was elevated in FND compared with healthy ( g = 0.90, 95% CI 0.66–1.14, I 2 = 70%) and neurological controls ( g = 0.56, 95% CI 0.19–0.92, I 2 = 67%). Greater psychoform dissociation was observed in FND samples with seizure symptoms versus healthy controls ( g = 0.94, 95% CI 0.65–1.22, I 2 = 42%) and FND samples with motor symptoms ( g = 0.40, 95% CI −0.18 to 1.00, I 2 = 54%). Somatoform dissociation was elevated in FND versus healthy controls ( g = 1.80, 95% CI 1.25–2.34, I 2 = 75%). Dissociation in FND was associated with more severe functional symptoms, worse quality of life and brain alterations. Conclusions: Our findings highlight the potential clinical utility of assessing patients with FND for dissociative symptomatology. However, fewer studies investigated FND samples with motor symptoms and heterogeneity between studies and risk of bias were high. Rigorous investigation of the prevalence, features and mechanistic relevance of dissociation in FND is needed.